2015
DOI: 10.1186/s12885-015-1803-y
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Homologous Recombination by insulin-like growth factor-1 inhibition sensitizes cancer cells to PARP inhibitors

Abstract: BackgroundImpairment of homologous recombination (HR) is found in close to 50 % of ovarian and breast cancer. Tumors with BRCA1 mutations show increased expression of the Insulin-like growth factor type 1 receptor (IGF-1R). We previously have shown that inhibition of IGF-1R results in growth inhibition and apoptosis of ovarian tumor cells. In the current study, we aimed to investigate the correlation between HR and sensitivity to IGF-1R inhibition. Further, we hypothesized that IGF-1R inhibition might sensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Therefore, nuclear hormone receptor activation is PARP-dependent. Insulin-like growth factor (IGF)-1 signaling is potentiated by PARP inhibition (Amin et al 2015). Furthermore, PARP1 interferes with GLP-1 signaling that may interfere with insulin secretion from β cells (Liu et al 2011).…”
Section: Parps In Regulating Central and Peripheral Organismal Metabomentioning
confidence: 99%
“…Therefore, nuclear hormone receptor activation is PARP-dependent. Insulin-like growth factor (IGF)-1 signaling is potentiated by PARP inhibition (Amin et al 2015). Furthermore, PARP1 interferes with GLP-1 signaling that may interfere with insulin secretion from β cells (Liu et al 2011).…”
Section: Parps In Regulating Central and Peripheral Organismal Metabomentioning
confidence: 99%
“…Most important to the development of more effective IGF1R-targeted therapies, PARP regulation in the ER-positive MCF7 and HER2-positive BT474 cell lines is mediated via IGF1R (Kim et al 2015). Preclinical support for the use of dual IGF1R and PARP inhibitors is highlighted by a study that showed an increased sensitivity to olaparib by the addition of the IGF1R inhibitor, BMS-536924, in BRCA1-mutated (MDA-MB-436 and HCC1937) compared with BRCA1 wild-type (BT20 and MDA-MB-231) TNBC cell lines (Table 2) (Amin et al 2015). There is also compelling evidence that IGFBP-3 is involved in DNA damage repair, highlighting the need for further investigation of the role of IGF-1-signaling in the DNA repair process in breast cancer .…”
Section: Brca-mutated Breast Cancermentioning
confidence: 99%
“…Therefore, following DNA damage through single-strand breaks, inhibition of PARP-1 leads to accumulation of DSB’s in HR-deficient cells, such as BRCA1/2-mutated cells. This effect is toxic and induces apoptosis [ 16 20 ]. This mechanism of targeted therapy has been named synthetic lethality.…”
Section: Introductionmentioning
confidence: 99%